Neural mechanisms of affective matching across faces and scenes - Preckel, Katrin; Kirsch, Peter (Scientific reports, 2019)
The emotional matching paradigm, introduced by Hariri and colleagues in 2000, is a widely used neuroimaging experiment that reliably activates the amygdala. In the classic version of the experiment faces with negative emotional expression and scenes depicting distressing events are compared with geometric shapes instead of neutral stimuli of the same category (i.e. faces or scenes). This makes it difficult to clearly attribute amygdala activation to the emotional valence and not to the social content. To improve this paradigm, we conducted a functional magnetic resonance imaging study in which emotionally neutral and, additionally, positive stimuli within each stimulus category (i.e. faces, social and non-social scenes) were included. These categories enabled us to differentiate the exact nature of observed effects in the amygdala. First, the main findings of the original paradigm were replicated. Second, we observed amygdala activation when comparing negative to neutral stimuli of the same category. However, for negative faces, the amygdala response habituated rapidly. Third, positive stimuli were associated with widespread activation including the insula and the caudate. This validated adaption study enables more precise statements on the neural activation underlying emotional processing. These advances may benefit future studies on identifying selective impairments in emotional and social stimulus processing.
Gesehen am 16.08.2019